Duties and Competencies of Supervisors in Building an Inclusive Work Culture in Islamic Educational Institutions - Nur Hayati; Moh Fayyad AS; Ainul Yaqin (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
This article provides a detailed explanation of the roles, duties, and competencies possessed by educational supervisors in building an inclusive work culture within Islamic educational institutions. Educational supervision is considered an essential component of the education management system, aiming to ensure that all teaching, learning, and school management processes operate in accordance with national quality standards. This research employs a qualitative approach using the library research method, which involves collecting data through critical analysis of various academic sources such as books, journals, research reports, and regulations related to supervisory competencies. The results indicate that educational supervisors carry diverse responsibilities, including planning, organizing, directing, supervising, and evaluating the performance of teachers and educational staff. The key competencies required of supervisors include personal skills, managerial skills, academic ability, educational evaluation, research and development, as well as social skills. Among these, managerial and academic competencies play a particularly significant role in improving the quality of learning and the effectiveness of school management. By implementing professional, participatory, and data-driven supervision, Islamic educational institutions can develop a management system that is transparent, accountable, and oriented toward continuous improvement in the quality of education.